PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, MORALITAS INDIVIDU, DAN KEADILAN ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Kartika, Yulia; Inapty, Biana Adha; Waskito, Iman (Jurnal Aplikasi Akuntansi, 2024)
This research aims to examine the influence of the effectiveness of internal control, individual morality, distributive justice, and procedural justice on the tendency of accounting fraud in the OPD of Dompu Regency. The population in this study were all civil servants who worked at the OPD in Dompu Regency. This research sample was determined using the method purposive sampling with the criteria of officials who are responsible for regional financial management in 30 OPDs in Dompu Regency. The data in this research was obtained by distributing questionnaires to 120 respondents in 30 OPDs. Structural Equation Modeling (SEM) with SmartPLS 3.0 used for data analysis. The results of this research indicate that the effectiveness of internal control and procedural justice have a negative and significant effect on the tendency for accounting fraud. Meanwhile, individual morality and distributive justice do not have a significant effect on the tendency for accounting fraud. It is hoped that this research can contribute to additional literature regarding motives for action tendenciesfraud involving ASN, in terms of conceptfraud triangle theory andmoral development theory. Apart from that, the results of this study can provide additional information as input to the Dompu Regency Government in reducing or preventing the tendency of accounting fraud